Composition and Granulometric Distribution of Sediment in Sindulang–Bitung Karang Ria, Manado - Tikas N.P. Rasmo; Royke M. Rampengan; Wilmy E. Pelle; Rignolda Djamaluddin; Esther D. Angkouw; Carolus P. Paruntu (JURNAL PESISIR DAN LAUT TROPIS, 2025)
Beaches, as coastal landforms comprising unconsolidated sediments, are essential for coastal ecosystems and human activities. The physical characteristics of sediments, particularly grain size (granulometry), reflect the dynamics of sedimentation processes and coastal environmental conditions. This study aimed to describe the composition and analyze the granulometric distribution of sediments collected from the Sindulang to Bitung Karang Ria beach area in Manado City. Sediment samples were collected from nine points on April 28, 2025, at a layer depth of approximately 1 cm from the sediment surface. The sediments were classified using the Wentworth scale and statistically analyzed using the Folk and Ward formula. The results showed that the sediment was dominated by the Sand fraction, ranging from Fine Sand 0.125 mm (3 φ) to Very Coarse Sand 2 mm (-1 φ). The Mean Size (Mz) ranged from 0.445 mm (1.168 φ) to 1.777 mm (-0.829 φ), falling within the Medium Sand to Very Coarse Sand categories. Statistical parameters indicated Sorting (σ₁) was Moderate to Poor, Skewness (Sk) varied from Fine-Skewed to Strongly Coarse-Skewed, and Kurtosis (KG) ranged from Platykurtic to Leptokurtic. This pattern indicates the dominance of active depositional processes and inherent sediment stability in the studied area. Keywords: beach, sediment composition, particle size distribution, Sindulang, Bitung Karang Ria   Abstrak Gisik, sebagai bentuk lahan pesisir yang tersusun atas sedimen lepas, memiliki peran penting bagi ekosistem pantai dan kegiatan manusia. Karakteristik fisik sedimen, khususnya ukuran butir (granulometri), mencerminkan dinamika proses pengendapan dan kondisi lingkungan pesisir. Penelitian ini bertujuan mendeskripsikan komposisi dan menganalisis distribusi granulometri sedimen pada lahan gisik di kawasan Sindulang hingga Bitung Karang Ria, Kota Manado. Sampel sedimen diambil dari sembilan titik pada 28 April 2025 pada kedalaman lapisan ≈ 1 cm dari permukaan sedimen. Sedimen diklasifikasikan berdasarkan skala Wentworth dan dianalisis secara statistik menggunakan formula Folk dan Ward. Hasil penelitian menunjukkan bahwa sedimen didominasi oleh fraksi Pasir, dengan variasi ukuran dari Pasir Halus 0,125 mm (3 φ) hingga Pasir Sangat Kasar 2 mm (-1 φ). Rataan Empirik (Mz) berkisar antara 0,445 mm (1,168 φ) hingga 1,777 mm (-0,829 φ), yang termasuk dalam kategori Pasir Sedang hingga Pasir Sangat Kasar. Parameter statistik menunjukkan Penyortiran (σ₁) tergolong Sedang hingga Buruk, Kemencengan (Sk) bervariasi dari Asimetris ke Ukuran Kecil hingga Asimetris Kuat ke Ukuran Besar, dan Peruncingan (KG) berkisar dari Platikurtik hingga Leptokurtik. Pola ini mengindikasikan dominasi proses deposisi aktif dan stabilitas sedimen di kawasan yang diteliti. Kata kunci: gisik, komposisi sedimen, distribusi granulometri, Sindulang, Bitung Karang Ria